Stable carbon isotope as a signal index for monitoring grassland degradation - Yao, Hongyun (Sci Rep, 2016)
Grassland degradation due to overgrazing is common in many areas of the world. This study analyzed the potential of the stable carbon isotope (δ(13)C) value as a structural microcosmic index to monitor processes of grassland degradation. The δ(13)C values of plant leaves, roots and soils in non-grazed (NG) and over-grazed (OG) grassland were measured from samples collected from the seven types of grassland in China. We found that the leaf δ(13)C values of palatable species (δ(13)C(leaf)) and root δ(13)C values (δ(13)C(root)) in OG grasslands were reduced compared with those from NG grasslands. Furthermore, the δ(13)C(leaf) and δ(13)C(soil) were positive correlation with elevation and latitude, δ(13)C(root) was negative correlation with them at high altitude (3000~5000m), and δ(13)C(root) and δ(13)C(soil) were negative correlation with them at low altitude (0~2000m), respectively. Consequently, tracing of the δ(13)C variations in grassland ecosystem can provide a powerful tool to evaluate the degree of grassland degradation.